Gastronomy of Antioquia’s East region. A tourism product? - Ramírez Ceballos, Silvia Liliana; Ospina Álvarez, José Daniel (Science of Human Action (revista descontinuada), 2019)
Gastronomic tourism is gaining importance in different parts of the world. Under this premise, tours around indigenous food of a certain place are created in order to attract tourists, thus generating processes of globalization and development of local resources. The outcome of this initiative is the improvement of the quality of life in the region and the development of competitive strategies, allowing them to retain a share of the market and preserve culinary traditions. This research seeks to determine if the gastronomic tourism represents a business opportunity for the inhabitants of Antioquia’s East region. With these in mind, a non-experimental and descriptive research was designed, using reference to documentary and electronic information, interviews, and surveys; an analysis of the current offer and the preferences of visitors attracted to the area by cultural, religious and nature tourism was also conducted. The results show there is a variety of dishes offered in the region of Eastern Antioquia which are full of meaning, starting with their preparation, plating, and consumption, and linked to cultural elements. These are reasons that can be used for generating business opportunities and improving employment in its inhabitants.